Pengaruh Kompetensi Terhadap Kinerja Pegawai Melalui Disiplin Kerja pada Kantor Kecamatan Tambun Utara - Zaqiyah Nur Afifah; Supardi Supardi; Agus Dharmanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to measure the direct and indirect influence of competence on employee performance through work discipline. This research uses quantitative research methods with the subjects being employees of the North Tambun District Office. The population in this study was 43 employees and the sample size was 43 respondents using the saturated sampling technique formula. The design used in this research is hypothesis testing using the statistical tool SPSS version 26. The results of the research show that competence has no effect on employee performance with a t value of 1.411 > 2.01954, competence has an effect on work discipline with a t value of 3.983 > 2.01954, work discipline has an effect on employee performance with a t value of 5.627 > 2.01954, and the indirect influence of competence on employee performance through work discipline has an effect with a total effect value greater than the direct effect of 0.563 > 0.215.